Addressing Employment Obstacles for Young Syrian Refugee Women - Datta, Namita (World Bank, Washington, DC, 2020)
This Jobs Note is a result of collaboration between S4YE-Jobs Group and Rand Corporation (an S4YE partner) . It builds on research covering the three countries with the highest concentration of Syrian refugees displaced since 2011: Turkey, Jordan, and Lebanon. It is intended to inform policymakers and practitioners on the barriers that Syrian refugees, especially women, face in securing work to earn a livelihood. This Note highlights practical solutions that have been designed and implemented by the World Bank and other S4YE partners including ReBootKamp, Education for Employment-Tunisia, Youth Business International, and the International Labour Organization. While not specific addressing internally-displaced persons (IDPs) within Syria, this Note could serve as a blueprint for examining and addressing many of the same barriers women face in Syria.